(untitled) (Archives of Criminology, 1960)
Investigation has covered 100 recidivists between the ages of 18 and 21, serving their term in jail; its purpose was to bring to light the scope of social misfitting and delinquency of the individuals with whom delinquency and recidivism seem to be of recent origin. Investigation has covered the individuals domiciled in Warsaw, who have been punished for at least the second time after having reached the age when penal responsibility begins (i.e. their seventeenth year of age) and have gone to jail for at least the second time. The investigation, started at the end of 1956 and finished in the middle of 1958, was conducted in two Warsaw jails and three provincial ones. All young adult recidivists with a condemning sentence who were at that time in jail were investigated, without making any selection of the cases, apart from the criteria enumerated above. The investigation, however, has taken into consideration data from judicial records and prison records, as well as from the Convicts, Register. Talks with the mothers of the convicts have provided material concerning the family home, the diseases which the convicted person had gone through, his pre-school and school days, way of life, etc. Psychological and medical examination has also been carried out. Young adult recidivists have been examined on an average, from four to five times within a few hours. In the case of those of the investigated who have been released from prison before December 1st , 1958, follow-up studies were carried out, to comprise a period of from six months to one year. 1. In investigating 100 young adult recidivists past record it was established that as many as 79 of them had been previously tried by a juvenile court (even though the law-court which tried them after they had completed the seventeenth year of age knew about that in a mere 23 cases). Apart from that, another 12 had committed thefts during their minority without being prosecuted before the law-courts. Consequently a mere 9 of all the investigated began to commit criminal offences after they were 16. The beginnings of delinquency took place in 19 per cent of the cases before the tenth year of their rives, and in 68 per cent before the thirteenth; it is highly probable however, that in reality the beginnings of their delinquency were earlier than that. Investigation into the further destinies of 79 investigated persons who had been tried while still minors has established the fact that 85 per cent of their number found themselves in jail before the lapse of two years from the moment of being released from a house of correction, or from their last trial before a juvenile court. As far as the 43 investigated. persons are concerned who had previously been in institutions for delinquent boys (training schools), as many as 27 were arrested before the lapse of six months from their release from such an institution, 12 remained at large for periods ranging from six months to one year and only 4 from one year to two years. The total of the data concerning the number of trials before both juvenile and ordinary courts looked as follows: out of 100 recidivists 13 had been tried twice, 20 - 3 times, 29 – 4 times, 17 - 5 times, 11 - 6 times, 10 - 7 or more times. Consequently 67 per cent of the investigated had already been tried 4 or more times, and every fifth one of them - 6 or more times. As far as their first term in jail is concerned, 16 of the investigated found themselves in jail before having attained the age of criminal responsibility, as a rule owing to their having given false birthdata at the time of their arrest, 55 at the age of 17, 26 at the age of 18 and a mere 3 at 19 years of age. Nearly one half of the recidivists had spent more time in jail than at large (from the moment of having reached the age of criminal responsibility), while the longest spell at large between one arrest and the next amounted to: below six months with 49 per cent of the investigated, from six months to one year with 33 per cent, while it was more than one year with a mere 18 per cent. Taking into consideration the kind of offences committed, we may divide the material under investigation into the following groups: A. Young adult recidivists punished exclusively for offences against property (as a rule, thefts) - 39 cases. B. Young adult recidivists punished exclusively for offences against life and health (grievous injury to the body, and slight bodily harm, brawls, infringement of bodily inviolability as well as for insulting a functionary of the police). There were only 10 offenders who committed such offences out of , hooligan" motives only, among all those investigated. C. Young adult recidivists punished for offences against property as well as for grievous injury to the body and slight bodily harm, brawls, infringement of bodily inviolability and insult to police functionaries - 51 cases. A. As for the persons investigated who had been punished only for offences against property (nearly exclusively for theft), they began to commit offences at the age of from 9 to 12 years, i.e. earlier than the rest. The first thefts, as a rule, took place in the family home. The majority of the perpetrators had been punished several times for theft by a juvenile court; one half of these, recidivists are criminals whose principal source of income are thefts, and, all of them had spent more time in jail than at large. It should be emphasized that both recidivists belonging to this group and the remaining ones had, in an overwhelming majority of cases (91 per cent), lived in their parents’, or else their mothers’, homes, and were able to have their meals at home (70 per cent). B. The beginnings of delinquency with the persons investigated who have been punished only for infringement of bodily inviolability, damage to the body, brawls and insults to police functionaries are considerably later and take place about the thirteenth to the sixteenth year of age. Similarly, the rate of penalties inflicted is smaller, and the spells of liberty much longer than with the thief group. Nearly all such acts (accosting and beating up a passer-by in the street, insult by word of mouth or beating up a policeman, etc.) were committed while under the influence of drink. Nearly All of the investigated who belong to this group systematically abuse alcohol, and their delinquency is closely connected with their drunkenness. C. The most numerous group of persons convicted, those punished both for theft and for damage to the body, brawls, infringement of bodily inviolability and insult to a policemen, may be divided into two sub-groups: Sub-Group One, 30 strong, consists of individuals who commit more thefts then other offences. They do not fundamentally differ from the individuals who belong to the thief group, either as to the objects of theft and their value, or as to the method of committing their crime. Here, too, we have to do with individuals for whom thefts constitute their principal source of income. Sub-Group Two, 27 strong, is composed of the individuals who commit more offences of injury to the body, insulting policemen and similar offences commited out of so-called hooligan motives, than thefts. This group approaches the individuals discussed in point B. It is characteristic of them that 11 (out of a total of 15 recorded in our materials) of perpetrators of robbery are to be found in this group. In the material investigated by us robbery goes hand in hand almost exclusively with offences committed from hooligan motives. When we evaluate the general degree of social misfitting of 100 of the investigated we may state that as many as 82 per cent of them belong to the category of manifold recidivists, who, as a rule, work only, if at all, by fits and starts, and are in close connection with the criminal environment. Particularly bad in this respect was the case of 35 of the investigated. 2. In so far as the family environment of young adult recidivists is concerned, we meet with a large percentage (53 per cent) of half-orphans; out of that number in 39 cases it was the mother who took care of the person investigated, in 5 cases - the father, while in the remaining 9 cases there was a stepfather or stepmother. 79 of the fathers were workers (of which 34 unskilled ones), 16 – clerical workers, 5 had their own artisan workshops. The majority of the mothers also earned their living, as a rule, as unskilled workers. The extent of alcoholism in the families under investigation is very considerable: 38 of the fathers can be considered drunkards - for many years they have been systematically drinking, they get drunk several times a week, spend their wages on drink. In the remaining families 29 fathers drink, on the average, from twice to three times a week, while 32 drink only sporadically and do not get drunk. Taking into consideration the educational atmosphere of the home, as well as the state of care and control in the environment during the period of the minority of the persons investigated, it was established that in 58 families the whole set of educationally definitely harmful factors was present. 3. The data obtained during the investigation concerning the personality of young recidivists speak in favor of the view that the latter are characterized by features which prove their low psychical maturity, and, in particular, a domination of impulsive reactions, a considerable and uncontrollable thoughtlessness, acting in the wake of motives responsible for the desire to make the most of life, in the form of continual entertainments and adventures, and a desire to impose on one’s coevals. A striking thing here is a lack of planning, absence of reflections on their future life, as well as of any more serious considerations for work, which, with them, is not identified with the idea of any definite trade; there is also a failure to appreciate critically the effects of one’s own behavior. As far as the level of intelligence is concerned, only 11 of the investigated showed signs of mental deficiency. There were 18 individuals of more than average intelligence. A psychological and psychopathological analysis of the investigated shows that 39 of those recidivists are to be included in the category of persons with personality disorders, who are usually described by the name of psychopaths. Yet it does not seem possible, on the basis of the investigation, to delimit the cases which could be diagnosed as psychopathic from such in which the normal development of the personality has suffered serious disturbances, mostly as a result of serious psychical shocks and psychical conflicts during their childhood. There can be no doubt, however, that the psychical qualities of the investigated cannot be squeezed within the framework of even a broad norm adopted, that their personality has pathological traits which exert an essential influence upon their behavior. In comparison with this most numerous group of 39 of the investigated, who are usually approached from the point of view of psychopathy, other pathological cases are not numerous in the material under investigation: with 6 of the investigated we have to do with encephalopathy after skull lesions, with 4 - with psychical changes after an 3 encephalitis, while 3 of the investigated suffer from epilepsy. In analyzing the abnormal personality traits with these 39 recidivists, the following re-occurring psychical qualities and reaction attitudes (incidentally mentioned in conversation by the investigated themselves) have been met with: a great irritability, lack of self-control, a tendency to provoke conflicts owing to an impulsive pattern of behavior, considerable difficulties in trying to subordinate oneself to various kinds of discipline, frequent states of depression and bad feeling, o tension and anxiety. It ought to be emphasized that out of 39 recidivists with serious personality disorders there were as many as 30 cases of very bad family environment in childhood. Besides, in all this material in which the family home so frequently assumes a negative outlook, it is noteworthy how many of young adult recidivists showed no emotional attachment whatsoever to their parents, including a large percentage of individuals of a very aggressive attitude. Among 47 young adults of a definitely aggressive attitude there were 30 lacking any emotional ties with the family home, and among the others there were only 10 free from an aggressive attitude. It is a significant thing that it is precisely with those of the investigated, revealing clear tendencies to aggression, over-impulsive, uncontrolled, that, in comparison with the other investigated, the various emotional conflicts appear much more conspicuously conflicts going back to childhood days, caused by an atmosphere in the family home (a feeling of loneliness due to the lack of manifestations of any tenderer feeling on the part of the mother, jealousy of a brother or sister, because the father liked them better, experiences of fear evoked by the brutality of a drunken father and an ambivalent attitude towards him, etc.) 4. As far as their mode of life was, concerned, only 16 of the investigated, who worked systematically, led a life similar to that of the generality of young people of the same age and of similar social environment. With the remaining ones we find a definitely negative attitude to work, while 32 of them worked very unsystematically, and 52 did but odd jobs or did not work at all. An overwhelming majority of the investigated spent most of their time strolling about the town, sitting in restaurants or nighthouses etc. Alcoholism reached big proportions with 56 of the investigated. They drink at least four or five times per week and frequently get drunk, while the majority of this group drink, and get drunk, every day. All the sons of alcohol addicts belong to this group. 27 of the investigated drink alcohol from once to three times per week, and it is only of 17 of them that it can be said that they either do not drink at all, or else drink only on rare occasions. 5. In our investigation, problems concerning the penalty and prison have been taken into consideration, first and foremost, under two of their aspects: whether or not, and if so, to what extent, the penalty of imprisonment does act, as a deterrent upon the persons investigated, according to their own opinion, and what influence a spell in prison had previously exerted upon them. Nearly all of them (70 answers have been obtained) believe that a penalty of imprisonment can act as a deterrent only on those who have not been in prison yet. Afterwards, that deterrent action ceases, since the prisoner comes to the conclusion that , you can get used to anything and bear any conditions". All the investigated also think that a spell in prison, so far from favouring their reformation, derailed them even further. Questioned whether after serving their present penalty they would go on committing criminal offences, 45 of the investigated answered indecisively, while admitting the possibility of their further committing offences, 15 declared bluntly that they would go on stealing, and a more 10 asserted that they would never again appear in the dock (their previous offences had, as a rule, to do with alcoholism). After the investigation was terminated, the further destinies of the 100 young adult recidivists who had been investigated were checked and it appeared. That 42 of them still served prison sentences, 29 had been released and remained at large, while another 29 had been once more arrested after their release for the commission of a new crime. Of the latter group, 17 remained free less than six months, 9 - from six months to one year, and only 3 for more than one year. It ought to be emphasized that out of the 29 investigated persons who were not arrested again after having been released from prison, 10 had been free for only about six months at the time of the last follow-up study. The results of the investigation bear witness to the fact that 80 per cent of young adult recidivists systematically commit criminal offences and belong to the category of the socially entirely depraved. The fundamental conclusion boils down to the following questions: The prophylaxis of young adults recidivism is closely connected with the problem of the recidivism of juvenile delinquents and with the problem of the earliest possible interception of the process of the juvenile’s demoralization. With regard to recidivists aged from 17 to 20 the imprisonment penalty ought to be altogether eliminated and long-term educational-cum-correctional methods applied, similar to those used with older juveniles with a high minimum term (two years). Young adult recidivists ought to be submitted to detailed psychological and psychiatrical examination in order to find and apply the appropriate, individualized methods of re-education.